Perencanaan dan Penerapan Soft Skill Manajemen Waktu dalam Aktivitas Perkuliahan untuk Membangun Kemampuan Kerja Calon Lulusan - Nengsi, Ayu Rahma; Sartika, Didi (YASIN, 2021)
This research aims to help students manage their time wisely in their studies. Planning and implementing wise time management will really help students effectively, do all assignments quickly and can reduce themselves from stress in lectures, because assignments are piling up with tight deadlines. This research was conducted on IAIN Takengon students, with a total of 30 respondents. Respondents were randomly selected from students of the Islamic Education Management Study Program and Sharia Tourism Study Program. Research is carried out by providing materials and training related to tips on managing time wisely, so that students can effectively complete all assignments according to priorities. This will have implications for the time spent working on the task, without feeling rushed by the submission deadline. The results showed that students had not effectively followed the steps given to participants during the research process. The results of the evaluation which was carried out after 4 weeks after the training, informed that the participants tended to have problems with monitoring and evaluating the time management they planned. This is what causes many students to not be optimal in carrying out assignments because they do not carry out monitoring and evaluation in implementing the plans that have been prepared. Being the main cause of the task is not completed according to the previously planned deadline. But in general, on average all respondents already know how to do good time management, which they can follow the steps continuously, so that it can become a habit that helps their studies.